Analisis Kebutuhan: Pembelajaran Bahasa Inggris Berbasis Padlet di Teknik Mesin Universitas Islam Riau - Etfita, Fauzul; Wahyuni, Sri (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
Teaching materials are a set of tools or facilities that contain materials, methods and evaluations used by teachers or lecturers in learning. So far, the teaching materials released by several developers have rarely been in accordance with the needs of Mechanical Engineering students, where some of the teaching materials available still use general English. In this study, in order to compile an appropriate teaching material, researchers have conducted a needs analysis. Needs analysis is a fundamental aspect for English language lecturers for specific purposes (ESP) in identifying information or the main needs of students and investigating areas of student shortages. In line with this statement, this research is a case study design that aims to determine the needs of mechanical engineering students in learning English through Padlet at the Faculty of Engineering in the 2019-2020 academic year. The data in this study were collected from researcher observations, questionnaires and semi-structured interviews with 40 students and two English language lecturers in the Department of Mechanical Engineering. The results revealed that speaking and writing are the main focus of English skills in the Mechanical Engineering department and listening along with reading are the next English skills needed than others.